1995
DOI: 10.1128/jcm.33.4.1011-1013.1995
|View full text |Cite
|
Sign up to set email alerts
|

Absence of human papillomavirus sequences in ovarian pathologies

Abstract: The role of human papillomaviruses (HPVs) in ovarian epithelium (either normal or neoplastic) remains controversial. We have investigated by PCR the presence of HPV DNA in fresh tissue from ovarian neoplasms and in primary cell cultures established from either normal, benign, or malignant ovarian surface epithelia. None of the fresh samples and primary ovarian cultures contained HPV DNA sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Interestingly, three tumors were localized in the ovary. The presence of HPV DNA in ovarian cancers was reported by some researchers [Mai et al, 1996;Pins et al, 1997], while others found no HPV in several ovarian pathologies [Sworn et al, 1995;Trottier et al, 1995].…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, three tumors were localized in the ovary. The presence of HPV DNA in ovarian cancers was reported by some researchers [Mai et al, 1996;Pins et al, 1997], while others found no HPV in several ovarian pathologies [Sworn et al, 1995;Trottier et al, 1995].…”
Section: Discussionmentioning
confidence: 85%
“…In reviewing the reference list in these articles, we identified one more article. Of the 35 identified studies, 22 were considered relevant after thorough examination. The remaining 13 studies were excluded for the following reasons: they were case reports ( n = 4) ; the data from these were included in another study ( n = 3) ; the paper reported HPV prevalence in serum and not HPV DNA in ovarian cancer tissue ( n = 1) ; endometrial and ovarian cancer were not differentiated ( n = 1) ; the information about how data were acquired was inadequate ( n = 1) ; the study included fewer than five ovarian cancer cases ( n = 1) ; the study only included borderline tumors ( n = 1) or the study was retracted after publication because of an error ( n = 1) .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies included are presented in Table . In most studies, the subjects were women with ovarian cancer of epithelial origin , and ovarian cancer was classified into histological subtypes , serous ovarian cancer being the most common. Two publications failed to report the type of ovarian malignancy .…”
Section: Resultsmentioning
confidence: 99%
“…66,67 Previous studies have uniformly failed to demonstrate the presence of HPV in primary ovarian carcinomas. [68][69][70] Nevertheless, the view that these are metastatic has been challenged and discussed in the literature, the alternative being that the neoplastic change in the ovary occurs as a part of a field change to a common oncogenic insult. It is postulated that this may be facilitated by transtubal transfer of HPVinfected or transformed cells and disruption of the ovarian surface due to ovulatory injury in women in their reproductive years.…”
Section: Synchronous Cervical and Ovarian Neoplasmsmentioning
confidence: 93%